Empirical Study on Regulatory Effect of National Economic Policy and Disclosure-Based System on Malaysian IPOs - Foo, Yuen Ling (1999)
In Malaysia, new issues are reported to be highly underpriced which subsequently led to oversubscription. Since underpricing in the Malaysia capital market has been unique with the regulatory effect (Ariff et.al.), this study extend regulatory intervention effect, namely the New Economic Policy (NEP) in the period of 1970- 1990 and Disclosure-Based System from 18t January 1996 on Malaysian IPOs. Comparison on pre- and post- policy implementation results show that the average market-adjusted return on both short run and long run period are higher in the postpolicy period. In the short run, the results of average market-adjusted returns in preversus the post- NEP are 52.35 versus 112.01 on first day (t=3.25), 57.63 versus 105.78 on first week (t=2.61), 62.89 versus 106.09 on first month (t=2.24), 46.41 versus 105.06 (t=2.89) on third month and 37.28 versus 106.71(t=3.55) on the sixth month. In the long run, the average market-adjusted returns of pre-versus the postNEP are 21.19 versus 108.89 (t=9.24) on the first year, -4.79 versus 97.18 (t=6.57) on second year and 6.94 versus 73.41 (t=5.74) on the third year. Implementation of disclosure-based system has significantly reduced the underpricing. The results of average market-adjusted returns of pre-and postimplementation of the system are 139.65 versus 1.39 on first day (t=I1.60), 140.26 versus 1.34 (t=1O.56) on first week, 136.08 versus 1.33 (t=1O.08) on first month and 147.93 versus 1.69 (t=10.09) on sixth month. Therefore, the study concluded that regulations do have effect on Malaysian IPOs.